The Influence of The Need to Seek Variation and Consumer Dissatisfaction on Moving The Xiaomi Smartphone Brand in Padang City - Ramadhania, Ramadhania; Rina, Rina (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2022)
This research aims to determine and analyze the influence of the need to seek variety and consumer dissatisfaction on switching the Xiaomi smartphone brand in Padang City. This research method is descriptive quantitative. The sampling technique in this research was purposive sampling, the research sample was 100 respondents, the data collection method was using Google from. The data analysis techniques used are multiple linear regression, t test, F test and coefficient of determination. From the results of the multiple linear regression test, it is Y = 0.856 + 0.330X1 + 0.655X2 + e. The t test carried out showed that the need to seek variety (X1) and consumer dissatisfaction (X2) partially had a significant effect on switching the Xiaomi smartphone brand in Padang City (Y). The results of the F test prove that the need to seek variety and consumer dissatisfaction together have a significant effect on switching the Xiaomi smartphone brand in Padang City. The coefficient of determination was 73.1%, while the remaining 26.9% was explained by other variables not discussed in the research, such as product quality and company image. Keywords: The Need To Seek Variety, Consumer Dissatisfaction, And Brand Switching